2005
DOI: 10.1029/2004jg000007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of terrestrial ecosystems and topography on coastal CO2 measurements: A case study at Trinidad Head, California

Abstract: [1] Coastal stations are critical for interpretation of continental-scale CO 2 exchanges although the impacts of land and sea breezes, local topography, katabatic winds, and CO 2 transport from nearby terrestrial ecosystems are not well characterized. We applied a modeling framework that couples meteorological (MM5), land-surface (LSM1), and tracer models to investigate the impact of these factors on coastal CO 2 measurements. Model predictions compared well with measurements over 4 months at our case study si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…In winter, in addition to the lower boundary layer, the increase of fossil fuel consumption may also partly contribute to the higher CO 2 mole fractions. The maximum CO 2 mole fraction occurrence time at WLG, a global WMO background site, agrees with the MBL and those observed at sites of similar latitudes (Nakazawa et al, 1993;Riley et al, 2005;Thoning et al, 1989).…”
Section: Seasonal Variations Of Regional Co 2 Mole Fractionssupporting
confidence: 85%
“…In winter, in addition to the lower boundary layer, the increase of fossil fuel consumption may also partly contribute to the higher CO 2 mole fractions. The maximum CO 2 mole fraction occurrence time at WLG, a global WMO background site, agrees with the MBL and those observed at sites of similar latitudes (Nakazawa et al, 1993;Riley et al, 2005;Thoning et al, 1989).…”
Section: Seasonal Variations Of Regional Co 2 Mole Fractionssupporting
confidence: 85%
“…A recirculation of respired nighttime CO 2 fields, for which the term "3-D rectifier effect" was established (Riley et al, 2005;Pérez-Landa et al, 2007;Ahmadov et al, 2007) is demonstrated for the case 20 May, 2005 (Fig. 5).…”
Section: Resultsmentioning
confidence: 90%
“…The conclusions made by Geels et al (2007) impose severe limitations on the usability of continental CO 2 concentration data from short towers and mountain stations in inversions. Moreover one may also add coastal stations to the "difficult sites" list (Riley et al, 2005). As a result, the CO 2 inversions performed by the TransCom 3 inversion community down-weighted continental observations, assuming that the data contained too much "noise" (Gurney et al, 2004;Wang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Continental scale studies show that the forward simulation of CO 2 improved by increasing the horizontal resolution from a number of degrees (Gurney et al, 2002) to one degree or less (Geels et al, 2007;Parazoo et al, 2008). Further increasing the horizontal resolution to just a few kilometres in more limited domain studies (Dolman et al, 2006) was shown to improve the CO 2 mixing ratio simulation at observation stations in uneven and coastal terrain, because of the models ability to simulate mesoscale circulations, like sea breezes and topography induced katabatic flows (Nicholls et al, 2004;Riley et al, 2005;Van der Molen and Dolman, 2007;Sarrat et al, 2007;Ahmadov et al, 2009). This also avoids representation errors by resolving a larger part of the variability in the CO 2 mixing ratio Tolk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%